Adorno on authoritarianism and its transformations in the current far-right discourse - Viitahuhta, Taneli (Monitor ISH, 2023)
This article proposes a reading into the discourse of the current far-right, utilizing and updating Frankfurt School’s studies on authoritarianism. In the first part, the Finns Party is focused on and interpreted as a contemporary far-right party with structurally two-fold communication model and an audience that pertains to more radical and conservative followers. In the second part, this reading is given depth by examining it in the light of post-war Critical Theory, especially Theodor Adorno’s views on language, capitalism, and the unconscious, and how these become connected in ethnocentric agitation.
Keywords: Adorno, Theodor W.; Finska; notranja politika; politična desnica; politične stranke; skrajna desnica